Superhydrophobic property enhancement on guard ring micro-patterned PDMS with simple flame treatment. (9th March 2020) - Atthi, Nithi; Sripumkhai, Witsaroot; Pattamang, Pattaraluck; Thongsook, Oraphan; Meananeatra, Rattanawan; Saengdee, Pawasuth; Ranron, Norabadee; Srihapat, Arckom; Supadech, Jakrapong; Klunngien, Nipapan; Jeamsaksiri, Wutthinan
Abstract: In this study, a simple flame treatment was conducted to improve hydrophobicity of PDMS surfaces with a square guard ring (SGR) structure. In a scratch test, it was found that a surface with a pattern of circular rings and eight stripe supporters (C-RESS) (width: 2.0 μ m, height: 5.0 μ m) with the SGR structure (width: 20 μ m, height: 100 μ m) had the highest durability and no collapsing structures were found. After the surface with the pattern of the C-RESS with the SGR structure was simple flame-treated at 700 °C ± 20 °C for 20 s, a unique flower-like nano-structure was developed on the surface and average surface roughness increased from 210.5 to 450.4 nm. The C-RESS with the SGR structure exhibited superhydrophobic properties with water and ethylene contact angle of 159.2° ± 1.6° and 157.9°± 3.2°, respectively. The unique surface topology and nano-structure become attractive because of the combination of its high durability and excellent superhydrophobic properties. Therefore, the flame-treated surface with the pattern of the C-RESS with the SGR structure is expected to be one of the promising antifouling technologies in various applications.